Complete Genome Sequence of the Avian Paramyxovirus Serotype 5 Strain APMV-5/budgerigar/Japan/TI/75 - Hiono, Takahiro (Genome Announc, 2016)
Here, we report the complete genome sequence of the avian paramyxovirus serotype 5 strain APMV-5/budgerigar/Japan/TI/75, which was determined using the Illumina MiSeq platform. The determined sequence shares 97% homology and similar genetic features with the previously known genome sequence of avian paramyxovirus serotype 5 strain APMV-5/budgerigar/Japan/Kunitachi/74.